Entrepreneurial Human Capital and Organizational Productivity: a Systematic Literature Review - Elida Gultom; Yunia Wardi; Hendrik Heri Sandi; Susi Evanita (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Purpose – This study systematically synthesizes and critically evaluates the empirical literature on entrepreneurial human capital (EHC) to explain how entrepreneurial experience contributes to organizational productivity and firm performance through organizational mechanisms across different organizational contexts. Methodology/Approach – a systematic literature review (SLR) was conducted using the Scopus database. Peer-reviewed journal articles published in English between 2022 and 2026 were identified using a search strategy based on the CIMO (Context–Intervention–Mechanism–Outcome) framework. Studies were screened using predefined inclusion and exclusion criteria, assessed with the Mixed Methods Appraisal Tool (MMAT), and synthesized through narrative analysis. a total of 28 empirical studies met the eligibility criteria. Findings – Entrepreneurial human capital enhances organizational productivity and firm performance primarily through innovation capability, organizational learning, and managerial capabilities. The findings also show that these relationships are context-dependent, with stronger evidence in SMEs operating in emerging economies. However, current evidence is dominated by cross-sectional studies and SME contexts, limiting broader generalization and causal interpretation. Novelty/Value – This review extends the entrepreneurial human capital literature by shifting from a direct-effect perspective to a mechanism-based explanation. It develops an integrative conceptual framework that explains how entrepreneurial human capital, organizational mechanisms, and contextual factors interact to generate organizational outcomes, providing valuable implications for theory development, managerial practice, and future entrepreneurship research.